ASPECTS OF PROVIDING CATERING SERVICES IN THE CONDITIONS OF RURAL TOURISM IN POLTAVA REGION (Development Service Industry Management, 2025)
The article examines the peculiarities of providing catering services in the context of rural tourism in the Poltava region, in particular, the use of local products, traditional cooking technologies and the impact of modern gastronomic trends on the development of tourist settlements in the region. Domestic and foreign scientific sources were studied, a literature review of current trends in rural tourism and gastronomy was conducted. The activities of tourist farms in Poltava region, in particular "Lyalina Svitlytsia", "Vesela Sadyba", "Kozatskyi Stan", "Staryi Khutir" and others, are analysed and their contribution to the promotion of authentic Poltava cuisine is determined. It is found that the food in these establishments is characterised by the use of local raw materials, seasonal ingredients and the introduction of sustainable practices in culinary production.  Attention is paid to the activities of rural estates in the context of culinary trends, including «Local food», «Comfort food», «Go green», «Traditional cooking methods», «Vegan food». It is noted that such approaches contribute to environmental safety, support of local agriculture, preservation of cultural heritage and creation of competitive advantages of the region. The main challenges and prospects for the development of rural tourism in the Poltava region in the context of the war are considered. The main problems include limited access to resources, difficulties with logistics and reduced consumer solvency. At the same time, promising areas include the growing demand for organic food, the organisation of gastronomic festivals, government support for agritourism and the digitalisation of tourism services. Further research will focus on the development of rural tourism, assessing the effectiveness of the implementation of environmental standards in tourist food, and determining the role of local culinary traditions in creating an attractive tourist brand in the Poltava region.
Keywords: rural tourism; food services; gastronomic trends; local products; organic food; traditional cooking techniques